Assessing vulnerability and adaptive capacity to potential drought for winter-wheat under the RCP 8.5 scenario in the Huang-Huai-Hai Plain - Li, Yingchun; Huang, Huanping; Ju, Hui; Lin, Erda; Xiong, Wei; Han, Xue; Wang, Heran; Peng, Zhengping; Wang, Yanqun; Xu, Jianwen; Cao, Yang; Hu, Wei (Agriculture, ecosystems & environment, 2015)
Drought is one of the major climatic disasters intimidating winter wheat production in the Huang-Huai-Hai (3H) Plain of China. The yield damage caused by drought tends to increase in the future, indicated by a pronounced uprising of drought events under RCP 8.5 scenario in terms of its affecting magnitude and area. This paper presents a modeling approach by using crop model DSSAT and hydrological indices to assess the vulnerability of winter wheat to future potential drought, based on an integrated assessment of exposure, sensitivity and adaptive capacity. Our results demonstrate that Beijing, Tianjin, Hebei and Shandong are more exposed and sensitive to potential drought than other regions in 3H. Traditional irrigation has the greater benefits in northern 3H Plain than southern regions, but is still insufficient to impede the yield loss due to potential drought. Under RCP 8.5 emission scenario and the period of 2010-2050, the worst drought effect is projected to occur around 2030. More than half of 3H plain are subject to high drought vulnerability. With increasing drought risks, we suggest immediate and appropriate adaptation actions to be taken before 2030s, especially in Shandong and Hebei, the most vulnerable provinces of 3H plain.